365 things to make and do Usborne activities - Watt, Fiona (London : Usborne Publishing Ltd., 2007)
This vibrant craft book offers a creative activity for every day of the year, with 128 pages of fun, step-by-step projects. From paper crafts and painting to cooking and seasonal decorations, it uses simple instructions and colorful illustrations to inspire children to explore art and creativity using everyday materials. Suitable for a wide age range, it$1 (Bs ideal for keeping young hands and minds busy all year round.s
Keywords: General Works - Reference Book